Crossing the Great Divide: Rewritings of the U.S.-Mexican Encounter in Walter Abish and Richard Rodríguez - Maarten van Delden (Studies in 20th & 21st Century Literature, 2001)
In a 1978 essay on the relationship between Mexico and the United States, Octavio Paz suggested that the two countries were separated by a "perhaps insuperable" divide. Yet two recent works—Richard Rodríguez's collection of essays Days of Obligation: An Argument with My Mexican Father (1992) and Walter Abish's novel Eclipse Fever (1993)—offer evidence of a changing outlook on the U.S.-Mexican encounter. Abish and Rodríguez build upon the storehouse of images of the irreconcilable differences between the two nations. However, insofar as they play with and question these images, they draw attention to the unstable, fluctuating nature of the U.S.-Mexican encounter in the late twentieth century. Abish focuses on the prevailing inequality in the relationship between the U.S. and Mexico, and reflects on the distinctive traits of the national character of each of the two countries. Yet a variety of narrative strategies serve to block any reading of Eclipse Fever in terms of sharply differentiated group identities. Rodríguez repeatedly evokes commonplace contrasts between the two nations. Yet his reading both of a variety of cultural phenomena, and of his own trajectory as an individual, suggests a complex interweaving of the cultures of Mexico and the United States.
Keywords: border narrative; U.S.-Mexican border; Walter Abish; Richard Rodrígues; Days of obligation: an argument with my Mexican Father; Eclipse Fever; nationality; identity; controversy